Cultural Differences and Supervisory Styles - Carlisle, Arthur Elliott (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
Assuming that managerial techniques developed through experience in the domestic situation and through a synthesis of the research and writings of accepted writers in the field of management are too often taken by executives for immediate installation and ready acceptance by supervision in a different cultural setting, Mr. Carlisle decided, in 1966, to conduct a study to explore in three cultural settings the perceptions of managers of the approach used by their lower level supervisors in directing the work of employees. This paper is a presentation of this study and its findings.